2015
DOI: 10.2494/photopolymer.28.747
|View full text |Cite
|
Sign up to set email alerts
|

Development of a High-Intensity UV Exposure Apparatus under a High-Pressure CO<sub>2</sub> Gas Atmosphere to Manufacture Large-Area Porous Ultralow-k Polyimide Substrates for Flexible Print Circuits

Abstract: Ultralow-k (dielectric constant) films are promising substrates for next-generation flexible print circuits. Introducing numerous pores into the film can effectively reduce the substrate's dielectric constant because the relative dielectric constant of air is smaller than that of any polymer substrate. We recently developed a short-cycle time process employing high-pressure CO 2 and the CO 2 -tertiaryamine zwitterions in polyimide precursor solutions to create 1-3 μm pores of >70% porosity. However, the film s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The signal attenuation of the high-frequency signal was compared to a solid PI film. With the same length, width, and height of the microstrip line for the porous PI and the solid PI, it was observed that the porous PI substrate could reduce the signal attenuation [14].…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…The signal attenuation of the high-frequency signal was compared to a solid PI film. With the same length, width, and height of the microstrip line for the porous PI and the solid PI, it was observed that the porous PI substrate could reduce the signal attenuation [14].…”
Section: Introductionmentioning
confidence: 95%
“…An FPC was prepared using the same procedure as in our previous study [14]. The surface of porous polyimide film was treated by UV light for enhancing the wettability of the plating solution.…”
Section: Porous Polyimide Filmmentioning
confidence: 99%
See 1 more Smart Citation
“…To prepare the standard formulation (denoted in previous studies [5,24]), 1.58 g (8.53 mmol) of UV-curable 2-(diethylamino)ethyl methacrylate monomer (DEMA; TCI, Japan) and 0.201 g (0.577 mmol) of diphenyl(2,4,6-trimethylbenzoyl) phosphine oxide (photoinitiator; Irgacure TPO, BASF) were added to 6.56 g of the PAA solution and stirred until a homogeneous solution was obtained. To clarify the effect of monomer concentration on pore structure, the monomer concentration was reduced from that used in the standard formulation.…”
Section: Methodsmentioning
confidence: 99%
“…However, the increasing demand for mobile devices capable of faster data transfer requires the use of PI FPCs with low dielectric constants to decrease signal attenuation. Therefore, dielectric constant reduction has been investigated by several researchers, as summarized in prior studies [1,2] and reviews [3,4] and in our previous articles [5,6].…”
Section: Introductionmentioning
confidence: 99%